Chronosequence on Natural Regeneration in Remnant Forest and Secondary Succesional Forest after Goldmining in the Amazon Rainforest of Madre de Dios, Peru - Morales Parra, Edson James (2020)
Gold extraction via small scale mining in the Amazon rainforest of Peru has become one of the greatest threats to deforestation and land degradation in the Amazon, especially in the Madre de Dios region which is one of the last biggest remnants of continuous tropical rainforest in the world. Restoration of these degraded ecosystems have become a priority in the last decade but without concrete actions, however, few research has been conducted in response to these restoration activities nor natural regeneration. The significance of this research was to 1) To Analyze how gold mining affects forest structure, species richness and diversity in the Amazon Rainforest of Madre de Dios, Peru. 2) To assess variation on diversity levels in secondary successional forest compared to that found in primary forest 3) to identify variations in the gold extraction methods reported in the region and how it affect forest recovery 4) to outstand the importance of remnant forest, if present, in nearby areas and finally 5) explore the existence of other factors that may prevent forest recovery after sever disturbances in four active gold-mining sites in Madre de Dios- Peru (Paolita-PA; Santa Rita-ST; San Jacinto-SJ and Aide-A. Sites were chosen depending on its management and the proximity to nearby remnant forest. Floristic composition of natural regeneration following abandonment of mining activities was studied by establishing a total of 21 plots (20x50m each) from which 8 plots were considered as primary-remnant forest and 13 plots were secondary growth forest spanning a period of 2 to 16 years of growth A total of 1404 individuals were described, representing 182 species scattered in 50 families from which only 21 species represented 50% of the total species found during the survey. To analyze biodiversity and similarity composition, Shannon and Jaccard indexes were used, respectively from which it was found that, the reduction of diversity within stages of succession confirms, as for this thesis, that diversity does not increases with time but instead, it decreases as the plot ages due additional factors over plots with more than five years after the cease of mining. As for variations in method of gold extraction, results did not shown significant variations in forest development that could be related to method of gold extraction but instead, climate might be playing an important role in forest development.